IMPLEMENTASI METODE TALQIN DALAM PEMBELAJARAN TAHFIDZ AL-QUR'AN PESERTA DIDIK KELAS 1 SD DI SD AL MADINAH BELIMBING - Syahla Aulia Zahra; Danang Dwi Basuki (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the implementation of the talqin method in learning Tahfidz Al-Qur’an for first-grade elementary school students at SD Al Madinah Belimbing, to identify the supporting and inhibiting factors, and to determine the effectiveness of the talqin method in helping students memorize the Qur’an. This study used a qualitative approach with a descriptive research type. Data collection techniques were carried out through observation, interviews, and documentation. The research subjects consisted of Tahfidz teachers and first-grade students at SD Al Madinah Belimbing. The results of the study showed that the implementation of the talqin method was carried out through several stages, namely learning preparation, implementation of the talqin method, and memorization evaluation. In the implementation stage, the teacher recited the verses of the Qur’an slowly and clearly according to the rules of tajwid, then the students repeated the recitation several times until they memorized it. Evaluation was carried out through students’ memorization deposits to the teacher. The talqin method proved to help students memorize the Qur’an more easily because it is in accordance with the characteristics of early-age children who learn through listening, imitation, and repetition. Supporting factors in the implementation of the talqin method include the competence of Tahfidz teachers, a religious school environment, regular Tahfidz schedules, and parental support in muroja’ah activities at home. Meanwhile, the inhibiting factors include differences in students’ memorization abilities, lack of concentration, limited learning time, and lack of repetition of memorization at home. Therefore, the talqin method can be used as an effective method in learning Tahfidz Al-Qur’an for elementary school students, especially lower-grade students.